PERUBAHAN PERILAKU BERBELANJA DARI PASAR TRADISIONAL KE PASAR MODERN DI KOTA MANADO DIPANDANG DARI ASPEK SOSIOLOGI - Marjam M. Pontorondo (Jurnal Ilmiah Al-Syir'ah, 2016)
This study about shopping behavior changes from traditional markets to modern market in the  Manado city is viewed from the aspect of sociology. This study used a qualitative approach. The results showed that the shopping behavior of most citizens of Manado city has changed shopping habits in traditional markets into shopping habits in the modern market. Everyone in the economic measures based on efficiency considerations that revolve around efficiency of money and space also efficiency of time and energy. Before someone decides to shop, his views always consider the fourth aspect of it, and then decided to act. Thus the action is determined by the orientation to the person's environment that is tailored to the needs inherent in him. Then someone can act as he wishes. Most citizens of Manado city construct behavior of shopping habits in traditional markets into shopping habits in the modern market. The peoples leaving the characteristics of cooperation and confidence in social economy action trough activity in the traditional market began to fade, tend to behave consumerist, individualistic, laden competition, but innovation and creative. The pattern of this kind of action can be a collective action at the subjective macro level. This means that changes in individual behavior of Manado city residents at a certain level in line with the rapid development and progress of science and technology, will have implications on fundamental social changes in the structure of social behavior overall Manado city residents. Manado, will become a city inhabited by modern society with a consumption-oriented economic measures or commonly known as the consumerist society.